Challenges in Competency Development of Islamic Religious Education Teachers in the Context of Education in Underdeveloped Regions: A Study on Senior High Schools in Papua - Nining Puji Lestari; Iqbal Saujan; Marwan Sileuw (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
Research on the development of professional competencies among Islamic Religious Education (IRE) teachers is still largely dominated by studies from regions with relatively adequate access to education. In contrast, peripheral regions such as Papua, which present geographical and social complexities, have not yet received much in-depth attention. The main purpose of this study is to identify and analyze the key structural, infrastructural, and cultural challenges that influence the competency development process of IRE teachers. This study employed a descriptive qualitative approach using a phenomenological method, through field observations and in-depth interviews with IRE teachers at three senior high schools in the City of Jayapura. Study results show that IRE teachers face structural challenges in the form of education policy that does not align and less accommodating to local conditions; infrastructural challenges in the form of limited facilities, technology, and financial support; as well as cultural challenges that include the low level of appreciation to the role of religious education teachers and dominance of local values that do not support education innovation The main finding of this study indicates that the development of professional competency among Islamic Religious Education teachers in Papua is hindered by interconnected structural, infrastructural, and cultural challenges, thereby necessitating a holistic and contextually grounded approach to teacher capacity building.